Biogas - Recent Advances and Integrated Approaches 2021
DOI: 10.5772/intechopen.91229
|View full text |Cite
|
Sign up to set email alerts
|

Dry Anaerobic Digestion for Agricultural Waste Recycling

Abstract: For sustainable agriculture, it is important to manage agricultural wastes, such as crop residues and livestock wastes. Anaerobic digestion has been gathering the attention to recycle these wastes into renewable energy (biogas) and fertilizer (soil amendment) (digestate). Dry anaerobic digestion is defined as digestion at higher than 20% of total solid (TS) content in the reactor, which is suitable for wastes with high TS content, such as agricultural wastes. In this chapter, we reviewed recent advances in bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 116 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…There was no lag phase in all the digesters as production commenced within the rst 24 hours which was indicative a good start up/hydrolysis stage in the DAD process. It has been observed that operating DAD at a higher F/I ratio could slow down the initial stage as shown elsewhere [10] but the results from this study revealed that the F/I ratios adopted were appropriate for rapid beginning phase of the DAD. Digester DAD6 peaked earlier (day 7) than other digesters with peak production of 280 ml.…”
Section: Daily and Cumulative Biogas Productionmentioning
confidence: 46%
See 1 more Smart Citation
“…There was no lag phase in all the digesters as production commenced within the rst 24 hours which was indicative a good start up/hydrolysis stage in the DAD process. It has been observed that operating DAD at a higher F/I ratio could slow down the initial stage as shown elsewhere [10] but the results from this study revealed that the F/I ratios adopted were appropriate for rapid beginning phase of the DAD. Digester DAD6 peaked earlier (day 7) than other digesters with peak production of 280 ml.…”
Section: Daily and Cumulative Biogas Productionmentioning
confidence: 46%
“…Feedstock-to-inoculum ratio plays a signi cant role in process e ciency of DAD. It has been observed that operating DAD at a higher F/I could lead to process failure due to accumulation of volatile fatty acids (VFAs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…It could be obtained from the biological breakdown of organic substances that contain 40%-75% methane (CH 4 ), 15%-60% CO 2 , and trace amounts of hydrogen sulfide (H 2 S), ammonia (NH 3 ), nitrogen (N 2 ), and carbon monoxide (CO). Biogas production is commonly produced using an AD method (Galván-Arzola et al, 2021) by utilising food and garden wastes, landfill, sewage sludge, animal manure (Mong et al, 2020;Zhang et al, 2019), agricultural wastes (Pan et al, 2021a;Riya et al, 2020;Weide et al, 2020), and municipal solid wastes (MSW) (Lopes et al, 2021;Pera et al, 2021;Riya et al, 2020;Zulkifli et al, 2019) as a viable feedstock. LCB may be converted into biogas, which can then be utilised as a RE source for various purposes, including heat and power production.…”
Section: Biochemical Processes Of Lignocellulosic Biomass Utilisationmentioning
confidence: 99%
“…The main advantages of dry digestion include its simple and cost-efficient operation, low water requirement, the reduced need for the pretreatment of the feed material, not needing the solid–liquid separation of the digestate, and minimal nutrient loss [ 16 , 17 ]. Three main reactor types exist: the garage (batch), leach-bed (batch with percolation) and horizontal or vertical plug-flow (continuous) types [ 14 , 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%